Separation of Halal and Non-Halal Food Product Places by Retail Business Actors: Comparative Study of PP Number 42 of 2024 with The Dubai Food Code: Pemisahan Tempat Produk Makanan Halal dan Non-Halal oleh Pelaku Usaha Ritel: Studi Perbandingan PP Nomor 42 Tahun 2024 dengan Dubai Food Code - Fitri Ashari, Arfiana; Adi Sudiro, Amoury; Machmud, Aris (Dame Journal of Law, 2026)
The existence of unclear information on processed food product labels, especially related to halal ingredients, raises concerns for Muslim consumers who are entitled to get products in accordance with sharia. This study aims to study and compare the regulation of the separation of halal and non-halal product places by retail businesses based on Government Regulation No. 42 of 2024 and the Dubai Food Code. The method used is a normative legal approach with comparative legal analysis of the provisions of the two regulations. The results of this study indicate that although Indonesia has a legal basis regulates the obligation to physically separate halal and non-halal product palices, its implementation is still weak due to the absence of technical guidelines and structured supervision. In contrast, Dubai has established clear operational standards. Fields findings also reinforce the conclusion that retail businesses in Indonesia have not fully implemented the obligation of separation and transparency, as seen in products. This study recommends strengthening technical regulations and supervisory mechanisms at the retail level to protect the right of Muslim consumers as a whole.